Advances in application of ultrasound in meat tenderization: A review - Dong, Yixuan; Zhang, Hongzhi; Mei, Jun; Xie, Jing; Shao, Changbo (Frontiers in Sustainable Food Systems, 2022)
Tenderness could measure the eating quality of meat. The mechanism of muscle tenderization is becoming more and more important in the past decade. Since the transformation of muscle into edible meat requires a complex physiological and biochemical process, the related tenderization of meat can be beneficial to improve the meat quality. As a non-thermal processing technology with energy saving, environmental protection and strong penetration, ultrasonic treatment has been widely used in the tenderizing process of meat products. In this paper, the principle of meat tenderization, the ultrasonic technology and the application of ultrasonic technology in meat tenderization are summarized. The effect of ultrasonic technology on the tenderization of meat products is discussed from different perspectives (muscle fiber and connective tissue properties).